Pharmacogenomics in the newborn - Mirta Corsello; Iliana Bersani; Natalia Chukhlantseva; Andrea Dotta (Hygeia Press di Corridori Marinella, 2013)
Genetic variation is an important determinant affecting the individual response to drugs. Considering the high variability in each individual genotype, the development of individualized therapies, according to the intrinsic features of the single patient, represents one of the most challenging problems in pharmacology. Pharmacogenetics analyzes the relationship between drug response and individual genetic differences, while pharmacogenomics analyzes the effect of genetic variations in patients' response to different drugs. The aim of these two research fields is to predict either drug response or the potential for the development of drug-related side effects. In particular, an important endpoint of pharmacogenomics should be to identify which group of patients responds positively, which patients are nonresponders and who will develop adverse reactions for the same drug and dose. Nevertheless, the utility of the pharmacogenetic and pharmacogenomic information as predictor of the activity of a specific drug-metabolizing enzyme or transporter should be cautiously limited to those developmental periods in which genotype-phenotype concordance is known. This means that in the perinatal period a special attention on the peculiar pharmacokinetic properties typical of this life period should be guaranteed. This means that effective and safe drug administration during fetal and neonatal life should consider the interindividual genotypic variability leading to different expression and activity of various enzymes. Both pharmacogenetics and pharmacogenomics may have a crucial role in the achievement of an individualized medicine. Prospective clinical trials analyzing the utility, safety, and cost-effectiveness of an individualized medicine based on the individual genotype are required. Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research